2003
DOI: 10.1093/jxb/erg028
|View full text |Cite
|
Sign up to set email alerts
|

Early steps in the oxidative burst induced by cadmium in cultured tobacco cells (BY-2 line)

Abstract: The rapid generation of H(2)O(2) by Cd(2+)-treated plant cells was investigated in cultured tobacco (Nicotiana tabacum L.) BY-2 cells. The starting point for the generation of H(2)O(2) has been located at the cell plasma membrane using cytochemical methods. Treatment of the cells with diphenyleneiodonium (DPI) and imidazol, both inhibitors of the neutrophil NADPH oxidase, prevented the generation of H(2)O(2) induced by Cd(2+). These data suggest the involvement of an NADPH oxidase-like enzyme leading to H(2)O(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(103 citation statements)
references
References 36 publications
9
88
1
3
Order By: Relevance
“…In this sense, it is interesting to note that both SOD and CAT activities increased in Cd treated cucumber and it is widely agreed that plants resist oxidative stress by increasing components of their intrinsic defense system . Cadmium induced increase in activities of POX and CAT have been reported by several researches (Dixit et al, 2001;Olmos et al, 2003;Smeets et al, 2005;Rodriguez-Serrano et al, 2006;Singh et al, 2008). Kopyra and Gwozdz (2003) and Laspina et al (2005) have reported a decline in CAT activity under Cd stress.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this sense, it is interesting to note that both SOD and CAT activities increased in Cd treated cucumber and it is widely agreed that plants resist oxidative stress by increasing components of their intrinsic defense system . Cadmium induced increase in activities of POX and CAT have been reported by several researches (Dixit et al, 2001;Olmos et al, 2003;Smeets et al, 2005;Rodriguez-Serrano et al, 2006;Singh et al, 2008). Kopyra and Gwozdz (2003) and Laspina et al (2005) have reported a decline in CAT activity under Cd stress.…”
Section: Discussionmentioning
confidence: 78%
“…Alteration in the activity of antioxidative enzymes with Cd stress has been reported by a number of workers (Dixit et al, 2001;Olmos et al, 2003;Hsu and Kao, 2004;Laspina et al, 2005;Rodriguez-Serrano et al, 2006;Goncalves et al, 2007;Singh et al, 2008;Mishra et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar conclusions on SOD activities getting impaired at higher aluminium concentration, as much as 3.5 mM had also been reported previously by Sahu et al (2010). The initial high activity of SOD leads to accumulation of H 2 O 2 and as a result, higher H 2 O 2 concentration induces different peroxidases such as APX and GPX to balance its level (Olmos et al, 2003). APX activity was found to be increased under aluminium stress in both root and shoot ( Figures 4A and B) initially, with high activity in root.…”
Section: Resultsmentioning
confidence: 96%
“…In a previous study, Sinclair et al (2009) observed that peroxules are induced by exogenous applications of H 2 O 2 . Cadmium has been demonstrated to induce oxidative stress by accumulating ROS in different cell compartments such as the plasma membrane, mitochondria, and peroxisomes (Olmos et al, 2003;RomeroPuertas et al, 2004;Garnier et al, 2006). By using Arabidopsis lines deficient in RBOHs, it has recently been demonstrated that NADPH oxidases could be a primary source of ROS production in response to Cd treatment (Gupta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%